The Role of The Regional Disaster Management Agency in Responding to Floods - Fanzisam Midunof Waruwu; Masnia Ahmad (ARISTO, 2026)
This study examines the role of the Regional Disaster Management Agency (BPBD) of North Nias Regency in mitigating flooding in Lotu Subdistrict. The purpose of this study is to determine how the Regional Disaster Management Agency (BPBD) of North Nias Regency plays a role in mitigating flooding in Lotu Subdistrict. The method used in this study is a descriptive qualitative research method by analyzing data using role theory with five indicators, namely the role as a stabilizer, the role as an innovator, the role as a modernizer, the role as a pioneer, and the role as an implementer. The results of the study show that the Regional Disaster Management Agency of North Nias Regency faces several obstacles, such as having only 13 employees and 8 rubber boat operators, which limits its disaster management capabilities; only three employees have undergone disaster management training; and budget issues hinder the procurement of new equipment, resulting in only two functional rubber boats. This study has limitations, such as a lack of quantitative data to assess the effectiveness of socialization and education, as well as a lack of exploration of the roles of the community and volunteers. Further studies are recommended using a holistic approach with quantitative and qualitative methods, as well as expanding the focus on multi-stakeholder collaboration and the use of information technology to improve the capacity and effectiveness of the BPBD in an applicable manner. Keywords: Role;  BPBD;  Disaster Management;  Flood;